Cleaner production in the dairy industry: good practices in a dairy plant in the municipality of Valença – Rio and Janeiro, Brazil - FAGUNDES, Christina Maria Costa; SOUZA, Simone Lorena Quitério de; VEIGA, Lilian Bechara Elabras (Food Science and Technology, 2024)
The Brazilian dairy sector has great economic importance and is ranked fourth among world producers. The search for less environmental impact has led to good sustainability practices and the adoption of environmental management instruments, products, and processes with an emphasis on cleaner production (CP). In this sense, this article presents CP adoption in the dairy industry. A case study aiming to propose alternatives associated with CP good practices in the dairy industry was conducted in the municipality of Valença, Rio de Janeiro. Data collection was performed with the help of a form and direct observation. The good practices and CP opportunities previously adopted by the industry were identified. Then, five CP measures were proposed and implemented to improve the sustainability of the Minas Frescal cheese production process. Minas cheese was selected for the study due to its higher sales volume and the best profit margin. Other opportunities for improvement should be considered to continue the proposed actions, which include reduction of raw materials and energy and water consumption during production, increase in the company’s profit margin and competitiveness in the national and international markets, access to new market niches, and reduction of environmental-, social-, and health-related impacts.